CRIMINALIZATION POLICY ON THE ACT OF MAKING, PRODUCING, AND TRADING ILLEGAL FISHING CAPTURE EQUIPMENT - Farida, Ida; Katimin, Herman (Jurnal Bina Mulia Hukum, 2023)
The widespread use of illegal fishing capture equipment in the form of drag nets and drag nets which harm and endanger the sustainability of fish resources and the environment in Indonesian waters, cannot be separated from the act of making, producing, and trading. The research method used is a sociological juridical approach which is qualitative in nature, where this research uses a normative approach with a sociological approach as support. Based on the results of the research, criminalizing the act of making, producing, and trading becomes a crime, formulated in article 85A, which reads "Whoever deliberately brings, produces and trades illegal fishing equipment or illegal fishing aids that are not in accordance with the provisions referred to in Article 7 shall be punished with a maximum fine of Rp. 250,000,000.00 (two hundred and fifty million rupiah)”. So that law enforcers comprehensively apply the elements of the intended crime, including proving the elements of intentional wrongdoing, Actus Reus and Mens Rea, as well as excuses that eliminate a crime.